Regenerative Role of T Cells in Nerve Repair and Functional Recovery - Tang, Xiaoxuan; Li, Qiaoyuan; Huang, Tingting; Zhang, Han; Chen, Xiaoli; Ling, Jue; Yang, Yumin (Frontiers in Immunology, 2022)
The immune system is essential in the process of nerve repair after injury. Successful modulation of the immune response is regarded as an effective approach to improve treatment outcomes. T cells play an important role in the immune response of the nervous system, and their beneficial roles in promoting regeneration have been increasingly recognized. However, the diversity of T-cell subsets also delivers both neuroprotective and neurodegenerative functions. Therefore, this review mainly discusses the beneficial impact of T-cell subsets in the repair of both peripheral nervous system and central nervous system injuries and introduces studies on various therapies based on T-cellcell regulation. Further discoveries in T-cell mechanisms and multifunctional biomaterials will provide novel strategies for nerve regeneration.